2018
DOI: 10.1002/cbin.11017
|View full text |Cite
|
Sign up to set email alerts
|

CoCl2, a mimic of hypoxia, enhances bone marrow mesenchymal stem cells migration and osteogenic differentiation via STAT3 signaling pathway

Abstract: Mesenchymal stem cells homing and migration is a crucial step during bone fracture healing. Hypoxic environment in fracture site induces bone marrow mesenchymal stem cells (BMSCs) migration, but its mechanism remains unclear. Our previous study and studies by other groups have reported the involvement of signal transducer and activator of transcription 3 (STAT3) pathway in cell migration. However, the role of STAT3 pathway in hypoxia-induced cell migration is still unknown. In this study, we investigated the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
(58 reference statements)
3
19
0
3
Order By: Relevance
“…erefore, after STAT3 inhibitor treatment, endothelial cell lineages and their common progenitor cells were inhibited resulting in suppression of microvessel proliferation. It has been shown that the BMSCs in the bone marrow were inhibited by the inhibition of JAK2/STAT3 signaling which is consistent with our results [59]. Additionally, our results showed that, under hypoxic condition, the microvessels from the vascular endothelial cells were enhanced by STAT3 overexpression.…”
Section: Ch + Dmso Ch + Inhibitor Ch Controlsupporting
confidence: 93%
See 1 more Smart Citation
“…erefore, after STAT3 inhibitor treatment, endothelial cell lineages and their common progenitor cells were inhibited resulting in suppression of microvessel proliferation. It has been shown that the BMSCs in the bone marrow were inhibited by the inhibition of JAK2/STAT3 signaling which is consistent with our results [59]. Additionally, our results showed that, under hypoxic condition, the microvessels from the vascular endothelial cells were enhanced by STAT3 overexpression.…”
Section: Ch + Dmso Ch + Inhibitor Ch Controlsupporting
confidence: 93%
“…On the one hand, previous studies showed that hematopoietic and endothelial cell lineages share common progenitors that affect the proliferation and differentiation of bone marrow-derived or umbilical cord blood-derived endothelial progenitor cells, which in turn promote angiogenesis [56,57]. On the other hand, it is well known that the bone marrow is characterized by the cellular diversity and complex functions [58].Importantly, vascular endothelial cells play a critical role in microvessels of the bone marrow [59,60]. Some studies showed that STAT3 is expressed in vascular endothelial cells [19].…”
Section: Ch + Dmso Ch + Inhibitor Ch Controlmentioning
confidence: 99%
“…Interestingly, Cobalt(II) chloride, another HIF-stabilizer also increased osteogenic differentiation as recently reported (73). Nevertheless, the counteracting potential of DFO for GC-induced inhibition of osteogenic differentiation as shown in the present study, has not been reported, yet.…”
Section: Polyglycerol Sulfate-based Hydrogels As a Potential Releasinsupporting
confidence: 64%
“…This result corresponds with previous studies that reported the inhibitory effect of CoCl 2 on osteogenic differentiation in hDPCs (Laksana et al 2017) and hPDLCs (Osathanon et al 2015). However, it was found that CoCl 2 upregulated osteogenic gene expression in BMSCs (Yu et al 2018). Differences in cell types may contribute to such disparities.…”
Section: Discussionmentioning
confidence: 98%